Good Luck Glasses - London, Sara; Rogers, Jacqueline (New York, 2000)
Seven-year-old Nomi decides that she is lucky when the new glasses she gets help her see things more clearly.
"Cartwheel books."
"Grades 1 & 2"--cover.
Keywords: Eyeglasses; Fiction